HUBUNGAN PENGETAHUAN IBU DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS PERDAGANGAN KABUPATEN SIMALUNGUN - Damanik, Dermawani (Universitas Prima Indonesia, 2020)
Exclusive breastfeeding is breast milk that given to babies from birth for six months without and / or replace with other food or drinks. Exclusive breastfeeding can provide the immunity needed for the growth and development of infants. The purpose of this study was to examine the relationship between knowledge and exclusive breastfeeding at Perdagangan Health Center in Simalungun Regency. The population is in this study were all mothers who have infants aged 7-12 months who live at ​​Perdagangan Health Center in Simalungun Regency. The sample in this study was 115 respondents. The study was conducted from September 2 to October 1, 2019. The instrument in this study used a questionnaire created by the researcher. Statistical test is using Chi-square. The results of the study obtained at Perdagangan Health Center in Simalungun Regency that the majority of mothers' knowledge about exclusive breastfeeding is in the poor category of 78 respondents (67.8%), the majority of mothers do not provide exclusive breastfeeding, namely 92 respondents (80%). Statistical test results show that P-value is 0.01 <0.05, so that the null hypothesis (HO) is rejected, which means there is a significant relationship between maternal knowledge and exclusive breastfeeding. It is recommended that health workers who work in the area of ​​the mother and child area should improve education programs for pregnant and breastfeeding mothers to increase the knowledge and interest of mothers to breastfeed exclusively in the first six months of a baby's life.